DOI: 10.18297/etd/2530
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with self-care behavior in persons with heart failure.

Abstract: Al-Hammouri, Mohammed Munther, "Factors associated with self-care behavior in persons with heart failure." (2016).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 94 publications
(129 reference statements)
0
3
1
Order By: Relevance
“…Regarding the relationship between impulsivity and self‐care in persons with HF, the number of studies published regarding the phenomenon is very limited. Impulsivity was found as a significant predictor of self‐care maintenance in persons with HF 16,17 . This is inconsistent with the findings of the current study where we found that impulsivity predicts a different process of self‐care in persons with HF.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Regarding the relationship between impulsivity and self‐care in persons with HF, the number of studies published regarding the phenomenon is very limited. Impulsivity was found as a significant predictor of self‐care maintenance in persons with HF 16,17 . This is inconsistent with the findings of the current study where we found that impulsivity predicts a different process of self‐care in persons with HF.…”
Section: Discussioncontrasting
confidence: 99%
“…The limited literature pertinent to the effect of impulsivity on self‐care in persons with HF hinders making further comparisons. As mentioned earlier, this study area is still evolving and the results reported in this study and in other studies provide growing evidence regarding the role of impulsivity in predicting self‐care in persons with HF 16,17 …”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations